Electrochemical characterization of high frequency stimulation electrodes: role of electrode material and stimulation parameters on electrode polarization. (6th April 2018) - Ghazavi, Atefeh; Cogan, Stuart F
Abstract: Objective . With recent interest in kilohertz frequency electrical stimulation for nerve conduction block, understanding the electrochemistry and role of electrode material is important for assessing the safety of these stimulus protocols. Here we describe an approach to determining electrode polarization in response to continuous kilohertz frequency sinusoidal current waveforms. We have also investigated platinum, iridium oxide, and titanium nitride as coatings for high frequency electrodes. The current density distribution at 50 kHz at the electrode–electrolyte interface was also modeled to demonstrate the importance of the primary current distribution in supporting charge injection at high frequencies. Approach . We determined electrode polarization in response to sinusoidal currents with frequencies in the 1–50 kHz range and current amplitudes from 100 to 500 µ A and 1–5 mA, depending on the electrode area. The current density distribution at the interface was modeled using the finite element method (FEM). Main results . At low frequencies, 1–5 kHz, polarization on the platinum electrode was significant, exceeding the water oxidation potential for high amplitude (5 mA) waveforms. At frequencies of 20 kHz or higher, the polarization was less than 300 mV from the electrode open circuit potential. The choice of electrode material did not play a significant role in electrode polarization at frequencies higher than 10 kHz. The current density distribution modeled at 50 kHz is non-uniform and this non-uniformity persists throughout charge delivery. Significance . At high frequencies (>10 kHz) electrode double-layer charging is the principal mechanism of charge-injection and selection of the electrode material has little effect on polarization, with platinum, iridium oxide, and titanium nitride exhibiting similar behavior. High frequency stimulation is dominated by a highly nonuniform primary current distribution.